Design and fabrication of a germinated sesame roaster - ปานสาคร สุนัน; ลังกาพินธุ์ จตุรงค์; ทักแก้ว ศิริรัตน์; ซังฮี้ วรรณิกา; วงษ์ชมพู ธวัสชัย (Frontiers in Engineering Innovation Research, 2011)
This research is to design and fabrication of a germinated sesame rotary roaster which has a capacity of 1 kg. The roaster is constructed using double wall cylindrical chamber and wrapped with rock wool. The outer dimensions of the roaster are 38.4 cm diameter and 35.5 cm length. Two 1000 Watt are using for the energy source and installed opposite of the rotary roaster. In addition, cylindrical material chamber is fabricated by stainless wire mesh of 0.5 mm diameter. Ideally, the roaster concept was prior estimated using conventional criterion based on pan roasting which is considering of the physical and nutrition properties of germinated sesame seed. The results are shown that, the roaster could be heated up over 100 degree Celsius and the temperature could be also controlled at steady state during roasting process. The rolling speed could be adjusted at the range of 1-21 rpm. It was noted that the best speed of the roasted geminated sesame was 16 rpm. Regarding the experiment at 100 degree Celsius of the roasting temperature, germinated sesame seeds provided a good quality and flavor. Besides, the moisture content and whiteness values were decreased with roasting time increased, while color value (a-value and b-value) and browning index (BI) of germinated sesame seeds were no difference. The trend of GABA content of germinated sesame seeds was declined with higher and longer of roasting temperature and time, respectively. However, the GABA content of the germinated sesame seeds was higher than sesame seeds without germination.